2010
DOI: 10.1021/pr100812d
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development and Validation of a Novel Extraction Method for Quantitative Mining of the Formalin-Fixed, Paraffin-Embedded Tissue Proteome for Biomarker Investigations

Abstract: Annotated formalin-fixed, paraffin-embedded (FFPE) tissue archives constitute a valuable resource for retrospective biomarker discovery. However, proteomic exploration of archival tissue is impeded by extensive formalin-induced covalent cross-linking. Robust methodology enabling proteomic profiling of archival resources is urgently needed. Recent work is beginning to support the feasibility of biomarker discovery in archival tissues, but further developments in extraction methods which are compatible with quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 31 publications
2
72
0
Order By: Relevance
“…Indeed, the main concern about the use of these FFPE tissues is to apply a procedure that could give rise to the largest molecular information, compared to the one available using fr/fr tissues. Generally, fr/fr tissues give a higher number of proteins compared to FFPE tissues (Giusti and Lucacchini, 2013), but some studies reported a better proteins identifications recovery with FFPE tissues (Nirmalan et al, 2011;Palmer-Toy et al, 2005;Shi et al, 2006). These comparisons highlight the importance of the chemical treatments for efficient FFPE tissue preparation.…”
Section: Optimal Tissue Solubilization Towards Protein Extractionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the main concern about the use of these FFPE tissues is to apply a procedure that could give rise to the largest molecular information, compared to the one available using fr/fr tissues. Generally, fr/fr tissues give a higher number of proteins compared to FFPE tissues (Giusti and Lucacchini, 2013), but some studies reported a better proteins identifications recovery with FFPE tissues (Nirmalan et al, 2011;Palmer-Toy et al, 2005;Shi et al, 2006). These comparisons highlight the importance of the chemical treatments for efficient FFPE tissue preparation.…”
Section: Optimal Tissue Solubilization Towards Protein Extractionmentioning
confidence: 97%
“…50% trifluoroethanol (TFE) for lung tissue processing was also tested (Tian et al, 2009). Commercial solutions exist for FFPE tissue processing such as the acid-deteriorating detergent RapiGest (Nirmalan et al, 2011), Liquid Tissue MS protein Prep kit (Nakatani et al, 2012;Prieto et al, 2005), Qproteome FFPE tissue kit (Becker et al, 2007), NDME-U (Chu et al, 2005), and FFPE Protein Extraction Solution (Agilent Technologies, Santa Clara, CA). Moreover, all these treatments methods can be applied with a digestion step done on Microcon (Millipore, Billerica, MA) or Vivacon (Vivaproducts, Littleton, USA) units.…”
Section: Optimal Tissue Solubilization Towards Protein Extractionmentioning
confidence: 99%
“…Several quantitative proteomic techniques have been utilized to investigate FFPE tissues, such as trypsin-mediated 18 O labeling (2), isobaric tag for relative and absolute quantitation (iTRAQ) (39 -41), label-free quantitation (42)(43)(44)(45)(46), and chemical dimethylation (47). The successful application of iTRAQ and chemical dimethylation are especially noteworthy, as these labeling techniques target primary amines, which is of importance to N-terminal degradomic analysis.…”
Section: Enrichment Of N-terminal Peptides From Ffpe Specimens-mentioning
confidence: 99%
“…Technological advances such as protein/ antibody chips, depletion of multiple high abundance proteins by affinity columns, and affinity enrichment of targeted protein analytes as well as multidimensional chromatographic fractionation, have all expanded the dynamic range of detection for low abundance proteins by several orders of magnitude in serum or plasma, making it possible to detect the more abundant disease-relevant proteins in these complex biological matrices [63][64][65][66][67][68][69][70][71]. However, plasma and cell-extract based discovery research studies aimed to identify low abundance proteins (e.g.…”
Section: Important and Current Implications Of Phosphoproteomics In Dmentioning
confidence: 99%